Perjanjian Baku Pembiayaan Murabahah Perbankan Syariah Indonesia - Hamidah, Siti; Sukarmi; Yuliati; Suwardiyati, Rumi (WARKAT, 2022)
Buying and selling products with murabahah contracts are ranked first in financing practices in Indonesian sharia banks but receive particular attention regarding conformity with sharia principles and the position of consumers from a consumer protection perspective. In the framework of realizing "implementation and development of risk management, prudential principles, good corporate governance & sharia compliance" as well as encouraging the creation of a regulatory union, contract standards, products and transactions, in accordance with the recommendations of the Islamic Finance Service Board (IFSB), a study is needed to analyze the suitability of murabahah financing agreements in sharia banking in Indonesia with Islamic law and positive law. Through legal research, a study was carried out on Indonesian sharia banking murabahah contracts based on the legal principles that should be the basis. From the results of the analysis of murabahah financing contract clauses, there are several clauses that do not comply with Islamic law and positive law (Consumer Protection law and Civil law), including those relating to down payments (urbun), actions when customers are in trouble, as well as promising something that is uncertain. For the future. Likewise, based on the Consumer Protection Law, it does not support the creation of consumer protection which contains elements of legal certainty and information disclosure as well as access to information (Article 3 (d) UUPK). Apart from that, it also conflicts with consumer rights as regulated in Article 4 UUPK.